Knowledge production and learning effects using the example of living labs in Halle (Saale) and Mannheim - Knieling, Jörg; Kretschmann, Nancy; Nell, Rebecca; Pfau-Weller, Natalie (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
Rising average temperatures and more frequent occurrence of heat islands increase the vulnerability of urban society in Halle (Saale) and Mannheim. Dealing with the associated challenges requires not only locally adapted strategies, but in particular an interdepartmental approach and involvement of those affected. Living labs in both cities open up the possibility of testing this in a transformative process. This paper discusses the challenges that living labs are confronted with in terms of knowledge already in the finding phase and what needs to be taken into account to support this process in the best possible way.
Keywords: Real-world-laboratories; Knowledge production; Learning process; Accompanying research; Climate change adaptation; Halle (Saale); Mannheim